Multi-habitat carbon stock assessments to inform nature-based solutions for coastal seascapes in arid regions - Carpenter, Stephen; Evans, Claire; Pittman, Simon J.; Antonopoulou, Marina; Bejarano, Ivonne; Das, Himansu S.; Möller, Mona; Peel, Kate; Samara, Fatin; Stamoulis, Kostantinos A.; Mateos-Molina, Daniel (Frontiers in Marine Science, 2023)
Coastal ecosystems are integral to global carbon cycling and are increasingly recognised for their role in mitigating climate change. Within these ecosystems, the dynamics of carbon storage are diverse, varying significantly across different habitats. However, existing management strategies often focus predominantly on vegetated habitats neglecting the contributions of non-vegetated areas. We address this knowledge gap by providing a quantitative spatial assessment of carbon storage across coastal seascapes varying in plant biomass. Our comprehensive multi-habitat inventory of carbon stocks in the United Arab Emirates confirmed that mangroves are the largest carbon-storing habitat per hectare (94.3 t/ha), followed by saltmarshes (63.6 t/ha), microbial mats (51.6 t/ha), mudflats (46.8 t/ha), seagrass (32.5 t/ha), and coastal sabkha (31.0 t/ha).Mean carbon content in the top 50 cm of mangrove soils (53.9 t/ha) was similar to saltmarshes (52.7 t/ha), microbial mats (51.6 t/ha), and mudflats (46.8 t/ha). We highlight the importance of including non-vegetated habitats in carbon accounting and management strategies. Our findings suggest that a more context-specific whole-system approach is essential for guiding effective ecosystem management and designing ecologically meaningful Nature-based Solutions (NbS). Adopting this broader perspective in NbS can ensure more comprehensive conservation and restoration outcomes, which not only protect and enhance blue carbon ecosystems but also contribute to broader ecological and social benefits. This approach is pivotal for advancing our understanding of interconnected coastal ecosystems and their role in climate change mitigation.